Climate Risk Management in Agricultural Extension – Zambia Reference Guide - Dinku, Tufa; Hansen, James; Trzaska, Sylwia; Grossi, Amanda; Huyer, Sophia; Moore, Maya; Sakumona, Mushekwa; Sakala, Isabel; Lungu, Olipa; Mangaba, Darlington (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
This is a reference guide to the course on Climate Risk Management in Agricultural Extension in Zambia. Improvements in the weather and climate information available in Zambia provide new opportunities for agricultural extension personnel to help farmers better manage the risks that they face, and to adapt recommended technology packages to local climatic conditions. This 2-week course aims to equip agricultural extension workers to access, understand and incorporate climate information into their professional work. It is designed to provide foundational knowledge on climate and agricultural decision making; and practical tools to analyze climate-related risks, use appropriate weather and climate information to support agricultural decisions, communicate complex climate information effectively with farmers, and integrate climate services into agricultural extension activities. This course is designed for agricultural extension professionals who actively support farmers with information, advice and other services. It targets extension agents working at the ward and sub-county levels within Zambia’s public sector agricultural extension service, and non-government extension and advisory service professionals with a comparable background. Course activities require working knowledge of web browsers, Microsoft Word, Excel, and PowerPoint.